Dioxin-like activity of environmental compounds in human blood and environmental samples - Long, Manhai; Bonefeld-Jørgensen, Eva Cecilie (Chemosphere, 2012)
Dioxins and dioxin-like (DL) compounds are some of the most toxic chemicals being highly persistent in the environment. The toxicological effects of dioxins are mediated via the aryl hydrocarbon receptor (AhR). Compounds of diverse structure and lipophility can bind and activate AhR. The AhR transactivation bioassay is utilized in an array of projects to study the AhR-mediated activities of individual chemicals and mixtures and for epidemiological purposes. This review summarizes a series of studies regarding the DL-activity of single compounds and complex compound mixtures in the environment and humans. We found that some pesticides, plasticizers and phytoestrogens can activate the AhR, and the combined effect of compounds with no or weak AhR potency cannot be ignored. The significant DL-activity in the wastewater effluent indicates the treatment is not sufficient to prevent contamination of surface waters with dioxins. Our results from human studies suggest that the serum DL-activity reflect the complex mixture of persistent organic pollutants (POPs). Greenlandic Inuit had lower serum DL-activity level compared to Europeans, probably due to long distance from the dioxin sources and UV degradation of the high potent dioxin and/or the inhibitory effect of the high level of non-DL POPs. Selective bioaccumulation of PCBs in the food chain may contribute to the negative correlation between serum POPs and DL-activity observed in Greenlandic Inuit. Hence the AhR transactivation bioassay provides a cost-effective and integrated screening tool for measurement of the DL-activity in human, environmental and commercial samples.